E-065 "Rescue" Intracranial Stenting for Refractory Large Vessel (Re)occlusion in Acute Ischemic Stroke. (29th July 2016) - Toth, G; John, S; Elgabaly, M; Hussain, M; Bain, M
Abstract : Introduction: The use of intracranial stents for symptomatic cerebrovascular stenosis has been limited since the publication of recent clinical trials suggestive of elevated procedural risks. However, the utility of these devices for "salvage" therapy in acute stroke has not been well studied. Objective: To investigate the efficacy of intracranial stenting in acute ischemic stroke patients with large vessel occlusion, who failed to recanalize or continued to reocclude with standard thrombectomy methods. Methods: Retrospective data review and analysis. Data was collected in 2015–2016. Results: We identified 5 patients (3 males; mean age 45.2 years), who received intracranial stents during acute stroke intervention. Stents were utilized if vessel reocclusion occurred after thrombectomy (4 cases), or when recanalization could not be achieved with standard thrombectomy devices (1 case). Self-expanding stents were used in 3, and balloon-mounted stents were deployed in 2 cases. Intraprocedural abciximab, followed by postprocedural dual antiplatelet therapy was used in all cases to prevent in-stent thrombosis. Total procedure time was 116–162 min (mean 134.6 ± 19.8). First recanalization was achieved within 22–106 min (mean 47.8 ± 34.1). Final TICI 2 B or 3 recanalization was achieved in all 5 (100%) patients. Clinical follow-up ranged from 4 days to 8 months. No symptomatic intracranial hemorrhage occurred. Median preprocedure vs follow-up NIHSS were 19 vs 11, respectively. One patient with the longest recanalization time (106 min), and highest preprocedural NIHSS (27) died. Another patient with reocclusion a few hours after a previous thrombectomy procedure did not improve despite TICI 3 final recanalization. The other 3 patients (60%) showed clinical improvement: the median NIHSS has decreased from 14 to 7. Conclusion: Intracranial stent placement for refractory large vessel (re)occlusion in acute ischemic stroke is feasible with high technical success rate, however, this is not always associated with favorable clinical outcome. If refractory vessel occlusion or reocclusion is encountered during acute stroke intervention, early stent placement and recanalization may lead to more favorable outcome. Verification in a larger cohort is necessary. Disclosures: G. Toth: None. S. John: None. M. Elgabaly: None. M. Hussain: None. M. Bain: None.